A comparison between the usage of free and proprietary solutions for General-purpose computing on GPUs (GPGPU) - Amaral, Isabella B. do; vel Lejbman, Alfredo G. (Anais da Escola Regional de Alto Desempenho de São Paulo (ERAD-SP), 2023)
In this research project, we explore the usage of open-source and proprietary solutions for performing general-purpose computing on graphics processing units (GPGPU). We begin by categorizing projects them according to their descriptions using unsupervised machine learning. Then, we compare the performance and usability of the solutions in each category, proposing enhancements to better support the development of open-source GPGPU tooling.